A tertiary care prospective of epidemiology and aetiopathogenesis of acute pancreatitis - Dogra, Varun; Ahmed, Rabia Nazir; Gilkar, Ishfaq Ahmad; Mir, Irfan Ahmad (International Surgery Journal, 2022)
Background: Acute pancreatitis is a potentially lethal condition resulting from an acute inflammatory process in the pancreas usually manifested by upper abdominal pain and raised concentration of pancreatic enzymes in blood, urine and peritoneal fluid. Aims and objectives were to study the epidemiology and aetiopathogenesis of acute pancreatitis in Jammu region of Northern India. Methods: This was a descriptive cross-sectional hospital based study, conducted in the postgraduate department of surgery, Government Medical College Jammu for a period of 3 years and included all admitted patients with diagnosis of acute pancreatitis. The main outcome variable was to find the various etiological factors associated with acute pancreatitis. Results: In our study acute pancreatitis was found to be more common in younger people. Most of the patients in the study population were below 40 years of age. Majority of the patients presented first time to the hospital with the chief complaints of pain upper abdomen. In this study, we found that the two principal causes of acute pancreatitis in our population were gall stones and alcoholism which contributed a total of about 68% cases followed by other causes such as hyperlipidemia, drug induced pancreatitis, worm induced acute pancreatitis, post-surgical pancreatitis, post traumatic pancreatitis, and hypercalcemia. Conclusions: Acute pancreatitis is a disease with high morbidity and mortality, and is quite common in Northern India. As such there is a need to make our population aware regarding the impact of alcoholism and bad dietary practices in causation of acute pancreatitis.